SOSIALISASI DAN PENDAMPINGAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERKOTAAN DAN PEDESAAN DI KABUPATEN LOMBOK TIMUR - Victoria Kusumaningtyas Priyambodo; Zihaddiah Fitri Azzahra; Intan Juwita Hartini; Novia Rizki; Nungki Kartikasari; Paradisa Sukma (Jurnal Pengabdian kepada Masyarakat, 2025)
Rural and Urban Land and Building Tax (PBB) is collected and managed by the region, in this case by the Regional Revenue Agency. Based on a field survey conducted by the team, there are still many people in the East Lombok Regency area who do not understand the obligation to pay land and building tax, including the value of the tax object and the amount of the tax rate. In addition, since 2024 there has been an increase in the Taxable Object Sales Value (NJOP) of PBB in the East Lombok area. This community service activity aims to increase the tax knowledge of the community in the East Lombok area and to improve the fulfillment of PBB tax obligations through socialization. The proposed problem-solving plan is to record the taxpayer's house and assets, as well as socialization regarding the requirements and procedures for managing the SPPT PBB. The location of this community service activity was carried out in the Sakra District, East Lombok Regency. The community service team carried out this activity accompanied by officers from the East Lombok Regional Revenue Agency. This activity is carried out periodically by providing a schedule to each village in the Sakra District with the aim of going directly to the community to increase public knowledge about taxes and increase public awareness of the obligation to pay taxes.